Cannabidiolic acid prevents vomiting in Suncus murinus and nausea‐induced behaviour in rats by enhancing 5‐HT1A receptor activation. (25th February 2013) - Bolognini, D; Rock, EM; Cluny, NL; Cascio, MG; Limebeer, CL; Duncan, M; Stott, CG; Javid, FA; Parker, LA; Pertwee, RG
<x xml:space="preserve">Abstract</x> Background and Purpose To evaluate the ability of cannabidiolic acid (CBDA) to reduce nausea and vomiting and enhance 5‐HT1A receptor activation in animal models. Experimental Approach We investigated the effect of CBDA on (i) lithium chloride (LiCl)‐induced conditioned gaping to a flavour (nausea‐induced behaviour) or a context (model of anticipatory nausea) in rats; (ii) saccharin palatability in rats; (iii) motion‐, LiCl‐ or cisplatin‐induced vomiting in house musk shrews (Suncus murinus); and (iv) rat brainstem 5‐HT1A receptor activation by 8‐hydroxy‐2‐(di‐n‐propylamino)tetralin (8‐OH‐DPAT) and mouse whole brain CB1 receptor activation by CP55940, using [35S]GTPγS‐binding assays. Key Results In shrews, CBDA (0.1 and/or 0.5 mg·kg−1 i.p.) reduced toxin‐ and motion‐induced vomiting, and increased the onset latency of the first motion‐induced emetic episode. In rats, CBDA (0.01 and 0.1 mg·kg−1 i.p.) suppressed LiCl‐ and context‐induced conditioned gaping, effects that were blocked by the 5‐HT1A receptor antagonist, WAY100635 (0.1 mg·kg−1 i.p.), and, at 0.01 mg·kg−1 i.p., enhanced saccharin palatability. CBDA‐induced suppression of LiCl‐induced conditioned gaping was unaffected by the CB1 receptor antagonist, SR141716A (1 mg·kg−1 i.p.). In vitro, CBDA (0.1–100 nM) increased the Emax of 8‐OH‐DPAT. Conclusions and Implications Compared with cannabidiol, CBDA displays significantly greater potency at inhibiting vomiting in shrews and nausea in rats, and at enhancing 5‐HT1A receptor activation, an action that accounts for its ability to attenuate conditioned gaping in rats. Consequently, CBDA shows promise as a treatment for nausea and vomiting, including anticipatory nausea for which no specific therapy is currently available.